Description of the genetic collection of strawberry (Fragaria × ananassa Duch.) cultivars according to the components of their fruit antioxidant complex - E. V. Zhbanova; I. V. Luk’yanchuk (Труды по прикладной ботанике, генетике и селекции)
Background. Quality indicators, medicinal and prophylactic properties of strawberry fruits are largely determined by their chemical composition. In order to improve the breeding work, it is necessary to look for the sources of high-level accumulation of macro- and micronutrients in fruits.Materials and methods. Fruits of 101 accessions from the genetic collection of introduced foreign and domestic cultivars, elite and selected forms held by the I.V. Michurin Federal Science Center were used as the target research material. All of them were grown on the experimental plantations from 1994 through 2020. Their chemical composition (ascorbic acid and anthocyanin contents) was analyzed at the Laboratory of Biochemistry and Food Technologies according to the standard methods.Results and conclusions. The ranges of variability in the accumulation of primary components of the antioxidant complex in strawberry fruits in the environments of the Central Black Earth Region (Michurinsk) were measured: 30.1–102.3 mg/100 g for ascorbic acid and 3.6–124.5 mg/100 g for anthocyanins. The cultivars were ranked according to the analyzed chemical components. A majority of them were classified into the group with average vitamin C content (50.1–90.0 mg/100 g). The largest part (85.6%) of the studied cultivars accumulated anthocyanins within the range of 30.0–70.0 mg/100 g. Valuable genotypes with high levels of ascorbic acid (above 90.1 mg/100 g) were identified: cvs. ‘Kokinskaya zarya’, ‘Lirovidnaya’, ‘Sudarushka’ and ‘Zephyr’. As for anthocyanins (above 90.1 mg/100 g), cvs. ‘Alena’, ‘Istochnik’, ‘Pamyati Zubova’, ‘Privlecatelnaya’, ‘Rubinovy kulon’, ‘Torpeda’ and ‘Feyerverk’, plus the elite seedling 56-5 (“Rubinovy kaskad”), showed the best results. The identified genotypes are of interest both for consumers, as they yield highly vitaminized fresh fruits, and for breeders as source material for the development of cultivars with improved chemical composition.